Psicoterapia di gruppo a Padova nel 1960-62 - Anzilotti, Carlo (Il sogno della farfalla, 2010)
Introducing Fagioli’s article on insulinotherpy republished in this issue, the author briefly analyzes the first experiences Fagioli undergoes of group psychotherapy and the context in which it takes place finding its roots in a line of thinking that will give rise consequently to the scientific verbalization of the theory between 1970 and 1974 and the therapeutic practice of the Collective analysis.